Doctors' reflexivity in hospital organisations: The nexus between institutional and behavioural dynamics in the sociology of professions. (November 2017) - Correia, Tiago
This article seeks to provide a clearer picture of how the nexus between institutional and behavioural dynamics operates among doctors in hospital organisations. On the basis of qualitative, in-depth research conducted in a hospital organisation, with the focus on doctors from two wards, differences in their actions and discourses challenge the coherence associated with professional and organisational values found in the debates in the sociology of professions. Rather than denying these influences, the article relates them to the way professionals reflexively make use of their roles in situated circumstances. Therefore, it discusses not only the fact that the doctors' medical rationale is crisscrossed by a diversity of influences – ethics, management and the organisational culture and subcultures – but also that they make reflexive deliberations on the basis of interests related to specific contexts. The analysis builds on recent discussions in neo-institutionalism aligned with critical realism, in order to refine theoretical arguments on reflexivity while providing tools for future empirical research in the sociology of professions.